Current Clinical and Pre-Clinical Imaging Approaches to Study the Cancer-Associated Immune System - Mueller, Christopher G.; Gaiddon, Christian; Venkatasamy, Aïna (Frontiers in Immunology, 2021)
In the light of the success and the expected growth of its arsenal, immuno-therapy may become the standard neoadjuvant procedure for many cancers in the near future. However, aspects such as the identity, organization and the activation status of the peri- and intra-tumoral immune cells would represent important elements to weigh in the decision for the appropriate treatment. While important progress in non-invasive imaging of immune cells has been made over the last decades, it falls yet short of entering the clinics, let alone becoming a standard procedure. Here, we provide an overview of the different intra-vital imaging approaches in the clinics and in pre-clinical settings and discuss their benefits and drawbacks for assessing the activity of the immune system, globally and on a cellular level. Stimulated by further research, the future is likely to see many technological advances both on signal detection and emission as well as the image specificity and resolution to tackle current hurdles. We anticipate that the ability to precisely determine an immune stage of cancer will capture the attention of the oncologist and will create a change in paradigm for cancer therapy.